The Role of Social Work in National Development - Apollo Rwomire (Social Work and Society, 2025)
The approach in this paper will be to define social work and national development first and then try to establish the relationship between the two.Â  The various categories of social work and their presumed influence on the various aspects of development will then be discussed. Â Thereafter, the discussion will be directed to the overall effects of the process of social work, in its totality, on national development.